Business Ethics in the Digital Age: Building Trust in Online Transactions - Bahiroh, Eloh (PT FORMOSA CENDEKIA GLOBAL, 2024)
To build trust between businesses and consumers in the ever-evolving digital era, the application of business ethics is very important. This is especially true in the e-commerce industry. Although online transactions are easy, dangers such as fraud and data manipulation can harm business reputation and customer trust. In this article, we discuss how the application of business ethics such as autonomy, honesty, fairness, and self-respect as a foundation for sustainable business. In addition, the application of important aspects such as integrity, kindness, competence, and consistency can increase customer trust. Companies can build mutually beneficial relationships, increase customer loyalty, and ensure business sustainability amidst the increasingly fierce competition in the digital world by implementing these principles comprehensively.